Causes and Consequences of Widespread Genotypic Uniformity in the Invasive Aquatic Plant Butomus umbellatus - Dean-Moore, Chloe (2024)
Over the last century, the aquatic plant Butomus umbellatus has escaped its native Eurasian range and invaded along the Canadian-US border. There appear to be two diploid genotypes invading North America and previous genetic analyses have found almost no genotypic variation within or among introduced populations. In these populations, plants produce both asexual clonal bulbils and numerous viable seed, however, there is no evidence that seed successfully establishes. First, I test the hypothesis that populations are genetically uniform, then I investigate the following two potential factors limiting sexual reproduction in the invasive range, (1) that a climatic mismatch between the native and introduced ranges is preventing seedling germination and (2) that widespread clonal reproduction renders sexual progeny highly inbred thereby inhibiting recruitment via inbreeding depression. I conducted self-fertilizations, within and between distinct genotype crosses, but none of the recombinant progeny differed in the proportion of viable seed produced, total dry mass or bulbil production. These results are consistent with the previous genetic data which suggests that populations are genetically uniform and that the two distinct genotypes are closely related. I germinated seed under 4 temperatures (20º, 25º, 30º, 35ºC) and analyzed climate data from the genotypes’ introduced and native ranges. Germination was highest at 30ºC and this matched temperatures from the native range, but was much warmer than what B. umbellatus experiences in North America. This suggests that a climatic mismatch between the native and introduced range could be limiting sexual reproduction among introduced diploid populations. Finally, I compared the performance between 15 clonal lineages and 30 recombinant lineages derived from within-genotype crosses under two water depths. All aspects of growth were greater in shallow than deep water and clonal plants outperformed recombinant progeny. It’s also possible that bigger and faster growing bulbils ...